2021
DOI: 10.1016/j.psj.2021.101362
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, organ attributes, nutrient and caloric utilization in broiler chickens differing in growth rates when fed a corn-soybean meal diet with multienzyme supplement containing phytase, protease and fiber degrading enzymes

Abstract: Growth performance, organ weight, ceca digesta short chain fatty acids ( SCFA ), jejunal histomorphometry, tibia ash, apparent retention ( AR ) of components and caloric efficiency were investigated in broiler chicken strains differing in growth rate fed diets with multienzyme supplement ( MES ). The strains differed in estimated time to reach 2.1 kg BW: 37, 43, 47, and 50 d and were designated C, F, J, and N, respectively. A corn-soybean mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…23 . Accordingly, Mohammadigheisar et al 24 , demonstrated that the growth rate and the utilization efficiency of energy are closely linked in broilers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 . Accordingly, Mohammadigheisar et al 24 , demonstrated that the growth rate and the utilization efficiency of energy are closely linked in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…High-performance genotypes use most of the dietary energy for muscle development rather than for other metabolic processes (kinetics, reproduction, immune response, thermotolerance, etc.) 23 , 24 . Thus, the growth rate largely affects the metabolic activity in fast-growing chickens in terms of PUFA accumulation 25 and in modification of metabolic pathways 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The apparent retention ( AR ) of components, apparent metabolizable energy ( AME ) and AME corrected for nitrogen ( AMEn ) were calculated as described by Mwaniki and Kiarie (2019) . The digestible crude protein conversion ratio ( CPCR g/kg BWG) and calories conversion ratio ( CCR mcal/kg BWG) were calculated according to Mohammadigheisar et al (2021) . …”
Section: Methodsmentioning
confidence: 99%
“…Zakaria et al (2010) suggested that the ineffectiveness of adding multi-enzyme to organ weights can be associated with levels. Mohammadigheisar et al (2021) also reported that adding multi-enzyme to broiler diets increased the gizzard weight, however; the connection between that increase and multi-enzyme is hard to explain, and the increase in weight is instead associated with the structural form of the feed.…”
Section: Carcass Yield and Organ Weightsmentioning
confidence: 99%